Предмет: Алгебра,
автор: lina4142
сравните выражения -у+3х и 2у-х если х=-2; у=-3
Ответы
Автор ответа:
0
-9 и -8 получается что -9 больше, то есть 1 пример
Автор ответа:
1
Ответ:
-у+3х > 2у-х
Объяснение:
-у+3х = 2у-х
если х=-2; у=-3 , то
-(-3) +3(-2) = 2(-3) -(-2)
3-6 = -6 +2
-3 = -4
-у+3х > 2у-х
Похожие вопросы
Предмет: Математика,
автор: dostykislam
Предмет: Биология,
автор: ttooot
Предмет: Математика,
автор: fantasy145
Предмет: Литература,
автор: nikitkamedvede
Предмет: Математика,
автор: Артём6451